Capital Flows in the APEC Region - Reinhart, Carmen (Occasional Papers; Occasional Paper ;, 1995)
The developing economies of the Asia Pacific Economic Cooperation (APEC) have been the recipients of a considerable volume of capital inflows in the 1990s. Given the increased integration of capital markets, it is not surprising that monetary control became more difficult for many developing APEC economies. Formulating an appropriate policy response has naturally been important. The three papers that make up this Occasional Paper each examine different aspects of these issues.